Reinterpretation of Controversial Verses in Qasidah Burdah from the Perspective of Ahlus Sunnah Waljamaah Islamic Boarding Schools - Luqman, Luqman; Siddiq, Muhammad Yusuf; Rosmini, Rosmini; Safitri, Nuri; Slama, Fathi Ben (Al Irsyad: Jurnal Studi Islam, 2026)
The verses of Qasidah Burdah have long been debated, as some contemporary scholars argue that they contain elements of ghuluw (excessive veneration), polytheism, and the deification of the Prophet. This study seeks to reinterpret these controversial verses through the perspective of Ahlus Sunnah Waljamaah Islamic boarding schools, examining them from textual, spiritual, and social dimensions. This research employs a qualitative field approach, including interviews with religious scholars, direct observations in Islamic boarding schools, and analysis of relevant documents, books, and academic journals discussing interpretations of Burdah. The findings indicate that Ahlus Sunnah Waljamaah scholars do not understand Qasidah Burdah as a literal text promoting polytheism. Rather, it is viewed as a highly sophisticated literary work rich in symbolic language and rhetorical beauty. Expressions of praise toward the Prophet are interpreted as manifestations of love (mahabbah), means of tawasul, and instruments for moral and character education among students. In institutions such as Al-Khairat in Palu and Ar-Riyadh in Palembang, Burdah is recited regularly as a form of dhikr, spiritual therapy, and a practice that fosters communal solidarity. Its linguistic features, such as majaz (metaphor), kinayah (allusion), tashbih (simile), and tawriyah (double entendre), demonstrate its aesthetic depth. Furthermore, the recitation of Burdah functions as a religious ritual that strengthens Sufi traditions and serves as a means of seeking intercession (shafa‘ah) and blessings. Ultimately, this study highlights Qasidah Burdah as a spiritually meaningful literary work that supports a moderate theological understanding.